Downstream Behavioral and Electrophysiological Consequences of Word Prediction on Recognition Memory - Hubbard, Ryan J.; Rommers, Joost; Jacobs, Cassandra L.; Federmeier, Kara D. (Frontiers in Human Neuroscience, 2019)
When people process language, they can use context to predict upcoming information, influencing processing and comprehension as seen in both behavioral and neural measures. Although numerous studies have shown immediate facilitative effects of confirmed predictions, the downstream consequences of prediction have been less explored. In the current study, we examined those consequences by probing participants’ recognition memory for words after they read sets of sentences. Participants read strongly and weakly constraining sentences with expected or unexpected endings (“I added my name to the list/basket”), and later were tested on their memory for the sentence endings while EEG was recorded. Critically, the memory test contained words that were predictable (“list”) but were never read (participants saw “basket”). Behaviorally, participants showed successful discrimination between old and new items, but false alarmed to the expected-item lures more often than to new items, showing that predicted words or concepts can linger, even when predictions are disconfirmed. Although false alarm rates did not differ by constraint, ERPs differed between false alarms to strongly and weakly predictable words. Additionally, previously unexpected (compared to previously expected) endings that appeared on the memory test elicited larger N1 and LPC amplitudes, suggesting greater attention and episodic recollection. In contrast, highly predictable sentence endings that had been read elicited reduced LPC amplitudes during the memory test. Thus, prediction can facilitate processing in the moment, but can also lead to false memory and reduced recollection for predictable information.